Genitourinary Medicine trainees' experience and training needs in the management of patients disclosing sexual violence. (April 2014) - Sacks, Rachel; Emerson, Carol
The British Association for Sexual Health and HIV (BASHH) Sexual Violence group assessed the level of confidence of Genitourinary Medicine (GUM) trainees in managing patients disclosing sexual violence using an online survey. Twenty-eight percent of current UK GUM trainees responded. The results demonstrated wide variation in trainees' experience and confidence in managing these patients, which was dependent on the patient type, as well as the gender of the trainee and the number of years' experience the trainee had in the specialty. There were also differences in the reported availability of training in this specialist area. Regular accessible training in identification and management of patients disclosing sexual violence is recommended for GUM trainees.